Sociodemographic factors, environmental, community mobility and health indicators associated with the spread of COVID-19 and case fatality rate in Indonesia: an ecological study: 10.55131/jphd/2022/200202 - Rachmat, Omat; Setyadi, Sugeng; Kustanto, Andi (Journal of Public Health and Development, 2022)
On March 11, 2020, the World Health Organization (WHO) declared COVID-19 a global pandemic due to its Case Fatality Rate (CFR) and numerous determining factors. Therefore, this study aims to identify the sociodemographic, environmental, community mobility, and health indicators associated with the pandemic and CFR. The design applied is an ecological study with data collected from 34 provinces in Indonesia and analyzed using the Spearman correlation. The results showed that independent variables such as population, density, the number of workers engaged in micro and small enterprises, hotel rooms, stroke, diabetes, general practitioners, specialists, nurses, PHC per district, PHC plus, and COVID-19 referral hospitals were positive and significant to the COVID-19 cases (p<0.01). Poverty in rural areas, elderly in rural and urban areas, sanitation, and hypertension were positive and significant to COVID-19 cases (p<0.05). Retail and recreation, grocery and pharmacy, transit stations, and residential areas were negative and significant to COVID-19 cases (p<0.01). Population growth rate, workplaces, and poverty in rural areas were negative and significant to COVID-19 cases (p<0.05). Elderly in rural and urban areas, urban slum households, immunization, and hypertension were positive and significant to CFR (p<0.05). The government needs to prevent the spread of the virus in provinces, especially in areas with high population and density, increased elderly population, low immunization rate, poor sanitation, and a significant number of residents living with comorbidities, such as stroke, hypertension, and diabetes. Furthermore, beds, tents, emergency buildings, oxygen cylinders, and multilevel referral systems between health facilities need to be provided. The government also needs to limit the inflow of people abroad, optimize the Work from Home (WFH) policy, and limit community mobility outside the home, especially in Bali.